Deconstructing the Discourse of Nationalism: A Study of Amitav Ghosh’s The Shadow Lines: Unveiling the Illusions of Nationalism: A Close Reading of Amitav Ghosh’s The Shadow Lines (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Shadow Lines explores the conflict between nationalism and a migrant cosmopolitanism, of religion and nationality, of belonging and displacement, and necessity of suppressing memories that threaten to disrupt the tidy narrative of history and national identity. The novel focuses on nationalism, the shadow line we draw between people and nations, which is both an absurd illusion and a source of terrifying violence. But it also sees as illusions so many other demarcations and categories of human experience and understanding that it ends up attributing value and a higher reality to a sort of amorphous romantic subjectivity.